Real-life evaluation of incidence and clinical outcomes of COVID-19 among healthcare workers during pre-vaccination and post-vaccination periods: A cross-sectional impact study - Yusuf Emre Ozdemir; Aysegul Inci Sezen; Serkan Surme; Sevtap Senoglu; Zuhal Yesilbag; Meryem Sahin Ozdemir; Osman Faruk Bayramlar; Emine Ilay Duman; Nomin Bold; Habip Gedik; Kadriye Kart Yasar (Journal of Infection in Developing Countries)
Introduction: We aimed to evaluate the prevalence and clinical outcomes of COVID-19 in healthcare workers (HCWs) in the pre-vaccination and post-vaccination periods. In addition, we determined factors associated with the development of COVID-19 after vaccination.